Le partage de l’eau dans le monde : un enjeu majeur du xxie siècle - Frédéric Lasserre (Mélanges de la Casa de Velázquez)
For some decades now the question of conflicts linked to water sharing have been gaining in importance in several parts of the world. Demographic growth is of course an essential factor to be taken into account, with burgeoning agricultural demands to feed a rapidly-expanding population, but it is not the only one; factors of political culture are also operative in the growing demand for water. To these causes of increasing demand for a finite resource we must add others, arising from economic and political tensions, between States (whence the notion, in varying forms, of future «water wars» in the 21st century) but also between social groups and between political entities within the same States. The analysis of these conflicts highlights the importance of the notion of social adaptability for their resolution, and contrariwise the difficulty with which certain societies may be expected to adapt to the growing scarcity of water, provoking social divisions and internal conflicts much more than wars between States.